Construcción y puesta en marcha de centrifugadora vertical de metales - Aranda Angamarca, Carlos Armando (2010)
It was built, we tested mechanically a vertical centrifuge machine and later was used to make bronze SAE 64, a material that is used for machines of high loads and low speeds as the sugar mills and machines stone porters. Were tested alloy solidification with different speeds of centrifugation with at different Gs acceleration of gravity to improve the grain size and hence the mechanical properties.